Agglomerated stone with granular penetrating textures and preparation method of agglomerated stone

Through the granite preparation method of granite through grainy texture, the problems of single pattern of granite product and cumbersome manufacturing process are solved, efficient and low-cost production is achieved, product aesthetics and market competitiveness are improved, and workers' health risks are reduced. .

CN119241133APending Publication Date: 2025-01-03GUANGXI LISHENG STONE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411494721.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing granite products have single pattern and cumbersome manufacturing process, resulting in high cost, low efficiency and insufficient market competitiveness, and there is a risk of health threats such as silicone disease during the production process.

Method used

The granite preparation method is adopted to mix calcium carbonate powder, calcium carbonate sand and pigment powder, add unsaturated polyester resin and additives to form a granular material, and is produced through mold pressing and vacuum shock technology. Gangstone avoids complex surface treatment steps and directly forms natural textures during the production process.

Benefits of technology

It significantly improves the aesthetics and production efficiency of granite, reduces production costs, reduces dust hazards, enhances workers' health and safety and the market competitiveness of products, and meets diversified decoration needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241133A_ABST
    Figure CN119241133A_ABST
Patent Text Reader

Abstract

The invention discloses agglomerated stone with granular penetrating textures and a preparation method of the agglomerated stone, and belongs to the technical field of agglomerated stone production. The agglomerated stone with the granular penetrating textures is prepared by the steps of mixing a plurality of raw materials, selecting a part of the mixture, adding color paste to prepare a granular material, adding a main material to form the granular penetrating textures and the like. The agglomerated stone has the advantages of rich colors, high flexibility, simple steps, low production cost and the like. According to the agglomerated stone with the granular penetrating textures, the problems that the pattern color of the agglomerated stone is single, and the manufacturing process is tedious can be solved; the measured values of the bending strength and the compression strength of the agglomerated stone far exceed the standard values specified by the national standard JC / T 908-2013, the excellent product quality of the agglomerated stone is shown, and the requirements of popularization and application can be met.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The invention relates to the technical field of granite production, in particular to a granular granite with through-textures and a preparation method thereof. [Background technology]

[0002] Stone is mainly divided into two categories: natural stone and artificial stone. Natural stone comes from natural rock, which is mined and processed into blocks or plates. Its unique texture and high strength give it excellent practicality and decorative effects. However, with the increasing depletion of natural stone resources, mining difficulties have increased, transportation is inconvenient, construction requirements are high, and there are radiation risks. Problems have gradually become prominent. Therefore, in recent years, people have begun to devote themselves to the research and development of artificial stone.

[0003] Artificial stone is made of industrial raw materials through advanced scientific and technological processes, but the current artificial stone production process still faces challenges, such as the lack of diversity in the appearance of the output stone and the complex product manufacturing process. Among them, quartz stone, as one of the common artificial stones, has the remarkable characteristic of high hardness. However, its production process is strictly restricted and mainly produced by the pressing plate method, that is, pressing one piece at a time. This not only leads to high production costs, but also takes a long time, occupies a large area, and puts pressure on corporate operations. What's more serious is that a large amount of silica dust will be generated during the production process of quartz stone. These high-hardness dusts are easily inhaled by the human body and difficult to discharge. Long-term accumulation can easily cause serious occupational diseases such as silicosis and pulmonary fibrosis, posing a great threat to workers' health.

[0004] Another type of artificial stone on the market, granite, focuses on pattern design. However, existing design patterns often fall into the dilemma of boring single colors or complex color stacking. Although attempts are made to add variety, the complexity of the manufacturing process is virtually increased, pushing up costs, and easily leading to aesthetic fatigue of the product, lack of market appeal and freshness. At the same time, complex manufacturing processes also reduce production efficiency, increase production costs, and further limit the market competitiveness of granite products.

[0005] In view of the above problems, the present invention proposes a granite with granular through-texture and a preparation method thereof. The granite manufactured by the preparation method has an intrinsically generated texture. Compared with traditional surface treatment technology, such as the method of printing texture on the surface adopted by Wadala Company in the United States, it is not only more natural and durable, but also avoids the appearance change caused by wear or shedding of the surface coating, ensuring the long-term aesthetics of the product. From the perspective of production technology, the present invention simplifies the manufacturing process and reduces production costs. The traditional method of mixing or surface treatment of multi-color materials requires not only high-precision mixing and spraying technology, but also additional subsequent processing steps to ensure the stability and beauty of the pattern. The granular through-texture of the present invention is naturally formed during the granite manufacturing process, without the need for additional surface treatment links, thereby reducing production time, site occupation and resource consumption, and significantly improving production efficiency and economic benefits. [Summary of the invention]

[0006] The main purpose of the present invention is to provide a granite with granular through-texture and a preparation method thereof, so as to solve the problems of the prior art such as the single color of the granite pattern and the complicated manufacturing process.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] A method for preparing granite with granular through-textures comprises the following steps:

[0009] (1) Pour calcium carbonate powder, calcium carbonate sand and pigment powder into the same stirring pot and mix them evenly;

[0010] (2) weighing unsaturated polyester resin and auxiliary agent, when step (1) is stirred for 4-6 minutes, first add the weighed unsaturated polyester resin into the same stirring pot, and then add the weighed auxiliary agent into the same stirring pot until they are evenly mixed;

[0011] (3) When the material is stirred into a particle size of 0-5 mesh and 3-5 mesh in step (2), a portion of the mixture in the stirring pot is taken out to make a small granular material with a through-texture, and the remaining material is continued to be stirred to make the main material;

[0012] (4) weighing unsaturated polyester resin and adding iron pigment to prepare a color paste used as a granular through-texture background;

[0013] (5) adding the accelerator to the color paste prepared in step (4), mixing thoroughly, adding the curing agent, and stirring evenly, and pouring it into the small material taken out in step (3), allowing the color paste and the small material to mix evenly to obtain a granular material;

[0014] (6) pouring the main material mixed in step (3) into the mold, leaving two gaps with basically the same width, different lengths and roughly the same direction;

[0015] (7) Pour the granular material prepared in step (5) into the gap for filling, vacuumize and vibrate, and then press after vibrating. After pressing and solidification, grind and polish to complete the production.

[0016] Furthermore, in step (1), the ratio of calcium carbonate powder to calcium carbonate sand is within 4:6-6:4, the calcium carbonate sand has a particle size of 85-95 mesh, and the pigment includes one or more of iron black, titanium dioxide, iron yellow, and iron red.

[0017] Furthermore, in step (1), the stirring frequency is 30-50 Hz, the speed is 40-300 r / min, and the stirring time is 15-20 min.

[0018] Furthermore, the auxiliary agent in step (2) includes one or more of a curing agent and an accelerator, the curing agent is methyl ethyl ketone peroxide, the accelerator is cobalt isooctanoate, the amount of the unsaturated polyester resin is 4%-10% of the total amount of calcium carbonate powder and calcium carbonate sand added in step (1), and the amount of the curing agent is 1.0%-1.3% of the unsaturated polyester resin added in step (2).

[0019] Furthermore, the amount of the small material taken out in step (3) is 10%-20% of the amount of the mixture prepared in step (2).

[0020] Furthermore, in the color paste described in step (4), the ratio of unsaturated polyester resin to iron-based pigment is between 2:3 and 1:1.

[0021] Furthermore, the amount of the curing agent added in step (5) is 1.0%-1.3% of the amount of the unsaturated polyester resin added in step (4), the amount of the accelerator is 0.2%-0.5% of the amount of the resin, and the viscosity of the prepared color paste is 900-1800mPa.S.

[0022] Furthermore, the vacuum degree during the vacuuming in step (7) is 0.093-0.097 Mpa, and the pressing time after shaking is 25-35 seconds.

[0023] Compared with the prior art, the present invention has the following technical advantages:

[0024] (1) The present invention has made innovations in the production process of granite. When making granite, a granular material directly derived from the main material of granite is added. Therefore, there is no color difference between the granular material and the main material, which makes the produced through-texture pattern appear particularly harmonious and unified, greatly improving the overall aesthetics of the granite. It is worth mentioning that the preparation method has high flexibility and can produce a variety of different colors according to the specific requirements and preferences of customers or consumers. This means that the color of the granular through-texture can be varied to meet various personalized decoration needs, adding more possibilities and creative space to the application of granite.

[0025] (2) Compared with the existing quartz processing technology, the production and processing process of the quartz preparation method of the present invention is simpler and more convenient. Due to the characteristics of the quartz raw materials, the production process does not require a complicated pressing process, thereby simplifying the production process, greatly reducing the production cost, and significantly shortening the production cycle. At the same time, this change also effectively improves the processing difficulty and noise problems, making the entire production process more environmentally friendly, efficient and safe.

[0026] (3) The dust generated during the production process of the granite in the present invention is less harmful than that of the prior art. Compared with the high-pressure pressing process used for hard materials such as quartz stone, the granite products of the present invention adopt a more gentle production method, avoiding the potential threat to human health from high-hardness dust (such as silicon dioxide) generated during the production process. If these dusts are inhaled for a long time, they are prone to cause serious occupational diseases such as silicosis. The production environment of this product is more friendly, reducing the emission of harmful substances, ensuring the health and safety of production workers, and also meeting the high standards of modern society for green and environmentally friendly production.

[0027] (4) Compared with products on the market that achieve similar effects through surface treatment technology, the present invention directly integrates granular materials into the production process, eliminating cumbersome post-processing steps. This "one-time molding" production method not only greatly shortens the production cycle, reduces site occupation and resource consumption, but also significantly reduces production costs. Especially in large-scale production, this efficiency improvement will be converted into a huge cost advantage, making the product more competitive in the market.

[0028] In summary, the granite product and granite preparation method of the present invention fully demonstrate their significant advantages over the prior art in terms of aesthetics, flexibility, simplicity and convenience, low cost, low time consumption, low harm, and protection of workers' health through innovation in pattern design, optimization of production efficiency and cost control, consideration of health and environmental protection, and improvement of market adaptability.

Brief Description of the Drawings

[0029] Figure 1 This is a picture of the finished product prepared in Example 1 of the present invention.

[0030] Figure 2 This is a picture of the finished product prepared in Example 2 of the present invention. [Specific implementation method]

[0031] The present invention will be further described in detail below in conjunction with specific embodiments. It should be emphasized that the following description is merely exemplary and is not intended to limit the scope of the present invention and its application.

[0032] A method for preparing granite with granular through-textures comprises the following steps:

[0033] (1) Pour calcium carbonate powder, calcium carbonate sand and pigment powder into the same stirring pot and mix them evenly;

[0034] (2) weighing unsaturated polyester resin and auxiliary agent, when step (1) is stirred for 4-6 minutes, first add the weighed unsaturated polyester resin into the same stirring pot, and then add the weighed auxiliary agent into the same stirring pot until they are evenly mixed;

[0035] (3) When the material is stirred into a particle size of 0-5 mesh and 3-5 mesh in step (2), a portion of the mixture in the stirring pot is taken out to make small particles with a through-texture. The remaining material is continued to be stirred to make the main material;

[0036] (4) weighing unsaturated polyester resin and adding iron pigment to prepare a color paste used as a granular through-texture background;

[0037] (5) adding the accelerator to the color paste prepared in step (4), mixing thoroughly, adding the curing agent, and stirring evenly, and pouring it into the small material taken out in step (3), allowing the color paste and the small material to mix evenly to obtain a granular material;

[0038] (6) Pour the main ingredients mixed in step (3) into the mold, leaving two gaps of basically the same width, different lengths, and roughly the same direction;

[0039] (7) Pour the granular material prepared in step (5) into the gap for filling, vacuumize and vibrate, and then press after vibrating. After pressing and solidification, grind and polish to complete the production.

[0040] The ratio of calcium carbonate powder to calcium carbonate sand in step (1) is within 4:6-6:4, the calcium carbonate sand has a particle size of 85-95 mesh, and the pigment includes one or more of iron black, titanium dioxide, iron yellow, and iron red.

[0041] The stirring frequency in step (1) is 30-50 Hz, the speed is 40-300 r / min, and the stirring time is 15-20 min.

[0042] The auxiliary agent in step (2) includes one or more of a curing agent and a accelerator, wherein the curing agent is methyl ethyl ketone peroxide, and the accelerator is cobalt isooctanoate. The amount of the unsaturated polyester resin is 4%-10% of the total amount of the calcium carbonate powder and the calcium carbonate sand added in step (1), and the amount of the curing agent is 1.0%-1.3% of the unsaturated polyester resin added in step (2).

[0043] The amount of the small material taken out in step (3) is 10%-20% of the amount of the mixture prepared in step (2)

[0044] In the color paste described in step (4), the ratio of unsaturated polyester resin to iron-based pigment is between 2:3 and 1:1.

[0045] The amount of the curing agent added in step (5) is 1.0%-1.3% of the amount of the unsaturated polyester resin added in step (4), and the amount of the accelerator is 0.2%-0.5% of the amount of the resin. The viscosity of the prepared color paste is 900-1800mPa.S.

[0046] The vacuum degree during the vacuuming in step (7) is 0.093-0.097 Mpa, and the pressing time after shaking is 25-35 seconds.

[0047] The preparation technology principle of granite with granular through-texture:

[0048] (I) Specific role and synergistic mechanism of raw materials

[0049] 1. Calcium carbonate powder and calcium carbonate sand: Calcium carbonate powder and calcium carbonate sand are the main fillers of granite. The difference in particle size (calcium carbonate sand is 85-95 mesh) and the ratio adjustment (between 4:6 and 6:4) achieve a perfect combination of coarse and fine particles, ensuring the basic strength and hardness of the granite. The fineness of calcium carbonate sand (particle size 85-95 mesh) provides the necessary structural support to ensure the strength and durability of the granite, as well as the uniformity of the material, and can form a delicate base texture in subsequent processing. Fine-grained calcium carbonate powder further fills the gaps between particles, improves the overall density and wear resistance, and enhances the density of the overall material. The synergistic effect of the two not only optimizes the physical properties of the material, but also lays a solid foundation for the subsequent texture formation.

[0050] 2. Unsaturated polyester resin: Its dosage is precisely controlled between 4% and 10% of the total amount of calcium carbonate powder and sand, ensuring that the resin can effectively bond the particles without excessively affecting the overall physical properties of the material. The addition of resin not only significantly improves the toughness of the granite, but also optimizes the processing performance and molding ability of the material, creating favorable conditions for the subsequent fine shaping of the texture. As the most important adhesive for granite, unsaturated polyester resin forms a tight bond between the silt sand, thereby enhancing the structural strength of the granite. It is worth mentioning that the strength of granite depends to a large extent on the performance of the resin; the higher the quality of the resin, the higher the strength of the granite. Therefore, when manufacturing silt sand board granite, medium and high quality resins are usually selected to ensure that the granite has superior performance.

[0051] 3. Curing agent methyl ethyl ketone peroxide and accelerator cobalt isooctanoate: The combination of these two is the key to resin curing, and together they accelerate the curing process of unsaturated polyester resin. The curing agent starts the cross-linking reaction of the resin to form a stable three-dimensional network structure, while the accelerator cobalt isooctanoate accelerates this process, reduces the activation energy of the reaction, and ensures that the ideal curing effect is achieved in a short time. Their dosage is precisely adjusted according to the amount of resin, ensuring that the curing process is both fast and uniform, avoiding internal stress concentration and shrinkage cracks, and ensuring the controllability of the curing process and the quality of the final product.

[0052] (II) Raw material dosage control and process optimization

[0053] In the process of preparing a granite with granular through-texture, precise control of the amount of each raw material is not only a technical requirement, but also a key link to ensure the quality and aesthetics of the final product. For example, calcium carbonate powder and calcium carbonate sand are the main fillers of granite, and their ratio directly affects the hardness and fineness of the finished product. A higher ratio of calcium carbonate sand can enhance the mechanical strength of the granite, while an appropriate amount of calcium carbonate powder helps to improve the uniformity and plasticity of the material. Unsaturated polyester resin is used as a binder, and its amount is between 4% and 10% of the total amount of calcium carbonate powder and calcium carbonate sand. Precise control of this range is crucial for the curing speed and strength of the granite. Too little may lead to insufficient bonding and affect the overall stability of the material; too much may make the material too soft and reduce the hardness. At the same time, the amount of curing agent (methyl ethyl ketone peroxide) and accelerator (cobalt isooctanoate) needs to be accurately proportioned according to the amount of resin added to ensure that the resin is fully cured within an appropriate time, neither too early to harden and cause internal defects, nor too slow to extend the production cycle.

[0054] In addition, the non-interchangeability of preparation steps and the optimization of process parameters are equally important. Each step has its specific purpose and effect. Once the order is changed or some steps are omitted, the quality and performance of the granite will be directly affected. For example, if the curing agent is added before the raw materials are mixed, the mixture will solidify prematurely during the stirring process and a uniform mixture cannot be formed; similarly, if the vacuum treatment is not fully performed, bubbles may remain in the finished product, affecting the appearance and strength. Therefore, strictly following the preparation steps and optimizing the process parameters are the key to ensuring the quality and production efficiency of granite.

[0055] In summary, the preparation of granite with granular through-texture is a complex and delicate process, which integrates knowledge and technology from multiple fields such as materials science and chemical engineering. By deeply understanding the mechanism of action of each raw material and their synergistic effects, and strictly controlling the amount of raw materials and process parameters, the present invention can prepare granite products that are both beautiful and practical, meeting the diverse needs of the market.

[0056] The following is a more specific example.

[0057] Example 1

[0058] A method for preparing granite with granular through-textures comprises the following steps:

[0059] (1) Pour 3000g of calcium carbonate powder, 2000g of calcium carbonate sand, and 30g of titanium dioxide into the same stirring pot until they are evenly mixed. The stirring frequency is maintained at 40 Hz, the speed is maintained at 200 r / min, and the stirring time is 16 min.

[0060] (2) Weigh 500 g of unsaturated polyester resin and 5 g of methyl ethyl ketone peroxide. When the stirring in step (1) is continued for 4 minutes, first add the weighed unsaturated polyester resin into the same stirring pot, and then add the weighed methyl ethyl ketone peroxide into the same stirring pot until the mixture is uniformly mixed.

[0061] (3) When the material is stirred into a particle size of 0-5 mesh and 3-5 mesh in step (2), 1000 g of the mixture in the stirring pot is taken out to make a granular small material with a through-texture, and the remaining material is continued to be stirred to make the main material;

[0062] (4) Weighing 32 g of unsaturated polyester resin and adding it to 48 g of iron yellow pigment to prepare a yellow color paste used as a granular through-texture background, and weighing 32 g of unsaturated polyester resin and adding it to 48 g of iron black pigment to prepare a black color paste;

[0063] (5) adding 0.06 g of cobalt isooctanoate to the color paste prepared in step (4) and mixing evenly, then adding 1 g of methyl ethyl ketone peroxide and stirring evenly, and then pouring into the small material taken out in step (3), allowing the color paste and the small material to mix evenly to obtain a granular material;

[0064] (6) Pour the main material mixed in step (3) into a mold with a length, width and height of 320 mm × 320 mm × 80 mm, leaving two gaps with a width of 20 mm, different lengths and roughly the same direction;

[0065] (7) Pour the granular material prepared in step (5) into the gap described in step (6) and fill it. After vacuuming and shaking, the vacuum degree is selected to be 0.095Mpa. After shaking, press for 25 seconds. After pressing and solidification, grind and polish to complete the production. The finished granite is shown in FIG. Figure 1 .

[0066] Example 2

[0067] A method for preparing granite with granular through-textures comprises the following steps:

[0068] (1) Pour 2500g of calcium carbonate powder, 2500g of calcium carbonate sand, and 30g of titanium dioxide into the same stirring pot until they are evenly mixed. The stirring frequency is maintained at 30 Hz, the speed is maintained at 270 r / min, and the stirring time is 20 min.

[0069] (2) Weigh 500 g of unsaturated polyester resin and 5 g of methyl ethyl ketone peroxide. When the stirring in step (1) is continued for 6 minutes, first add the weighed unsaturated polyester resin into the same stirring pot, and then add the weighed methyl ethyl ketone peroxide into the same stirring pot until the mixture is uniformly mixed.

[0070] (3) When the material is stirred into a particle size of 0-5 mesh and 3-5 mesh in step (2), 1200 g of the mixture in the stirring pot is taken out to make a granular small material with a through-texture, and the remaining material is continued to be stirred to make the main material;

[0071] (4) Weigh 90 g of unsaturated polyester resin and add it to 140 g of iron black pigment to prepare a black color paste used as a granular through-texture background;

[0072] (5) Add 0.16 g of cobalt isooctanoate to the color paste prepared in step (4) and mix evenly, then add 2.1 g of methyl ethyl ketone peroxide, stir evenly, and then pour into the small material taken out in step (3), so that the color paste and the small material are mixed evenly to obtain a granular material;

[0073] (6) Pour the main material mixed in step (3) into a mold with a length, width and height of 320 mm × 320 mm × 80 mm, leaving two gaps with a width of 20.2 mm, different lengths and roughly the same direction;

[0074] (7) Pour the granular material prepared in step (5) into the gap described in step (6) and fill it. After vacuuming and shaking, the vacuum degree is selected to be 0.095Mpa. After shaking, press for 30 seconds. After pressing and solidification, grind and polish to complete the production. The finished granite is shown in FIG. Figure 2 .

[0075] The bending strength and compressive strength of the granite obtained in Example 1 and Example 2 were tested according to the national standard JC / T 908-2013. The results are shown in the table below.

[0076] Experimental groups Bending strength(MPa) Compression strength(MPa) Example 1 30.2 100.1 Example 2 32.5 106.4

[0077] Note: The national standard JC / T 908-2013 stipulates that the bending strength of granite is ≥15MPa, and the national standard JC / T908-2013 stipulates that the compressive strength is >80MPa.

[0078] It can be seen from the above table that the bending strength of the granite in Example 1 and Example 2 can reach more than 30MPa, while the national standard JC / T908-2013 stipulates that the bending strength of granite is ≥15MPa; the compression strength of the granite in Example 1 and Example 2 can reach more than 100MPa, while the national standard JC / T 908-2013 stipulates that the compression strength is>80MPa. It can be seen that the measured values ​​of the bending strength and compression strength of the granite are far more than the standard values ​​stipulated in the national standard JC / T 908-2013, showing its excellent product quality, especially the bending strength, the measured value is more than twice the standard value, indicating that the granite produced by the preparation method of the present invention has excellent performance in anti-bending performance, and the measured value of compression strength also exceeds the standard value, further proving the high strength and durability of the granite. In summary, the granite produced by the preparation method of the granite with granular through-texture described in the present invention has excellent production quality, far exceeding the national standard requirements, and can meet the needs of promotion and application.

[0079] Those skilled in the art will recognize that numerous variations to the above description are possible, and that the examples are intended only to describe one or more specific implementations.

[0080] Although what is considered as exemplary embodiments of the present invention has been described and described, it will be understood by those skilled in the art that various changes and substitutions may be made thereto without departing from the spirit of the present invention. In addition, many modifications may be made to adapt specific situations to the teachings of the present invention without departing from the central concept of the present invention described herein. Therefore, the present invention is not limited to the specific embodiments disclosed herein, but the present invention may also include all embodiments and their equivalents that fall within the scope of the present invention.

Claims

1. A method for preparing granite with granular through-texture, characterized in that: The following steps are involved: (1) Pour calcium carbonate powder, calcium carbonate sand and pigment powder into the same stirring pot and mix them evenly; (2) weighing unsaturated polyester resin and auxiliary agent, adding the weighed unsaturated polyester resin into the same stirring pot after stirring for a period of time in step (1), and then adding the weighed auxiliary agent into the same stirring pot until the mixture is evenly mixed; (3) After the material is stirred into a certain particle size in step (2), a portion of the mixture in the stirring pot is taken out to make small particles with a through-texture, and the remaining material is continued to be stirred to make the main material; (4) weighing unsaturated polyester resin and adding iron pigment to prepare a color paste used as a granular through-texture background; (5) adding the accelerator to the color paste prepared in step (4), mixing thoroughly, adding the curing agent, and stirring evenly, and pouring it into the small material taken out in step (3), allowing the color paste and the small material to mix evenly to obtain a granular material; (6) pouring the main material mixed in step (3) into the mold, leaving two gaps with basically the same width, different lengths and roughly the same direction; (7) Pour the granular material prepared in step (5) into the gap for filling, vacuumize and vibrate, and then press after vibrating. After pressing and solidification, grind and polish to complete the production.

2. The granite with granular through-texture according to claim 1, characterized in that: The auxiliary agent includes one or more of a curing agent and an accelerator. The curing agent is methyl ethyl ketone peroxide, and the accelerator is cobalt isooctanoate.

3. The method for preparing granite with granular through-texture according to claim 1, characterized in that: The ratio of calcium carbonate powder to calcium carbonate sand in step (1) is within 4:6-6:4, the calcium carbonate sand has a particle size of 85-95 mesh, and the pigment includes one or more of iron black, titanium dioxide, iron yellow, and iron red.

4. The method for preparing granite with granular through-texture according to claim 1, characterized in that: The stirring frequency in step (1) is 30-50 Hz, the speed is 40-300 r / min, and the stirring time is 15-20 min.

5. The method for preparing granite with granular through-texture according to claim 1, characterized in that: The amount of the unsaturated polyester resin in step (2) is 4%-10% of the total amount of the calcium carbonate powder and calcium carbonate sand added in step (1), and the amount of the curing agent is 1.0%-1.3% of the unsaturated polyester resin added in step (2).

6. The method for preparing granite with granular through-texture according to claim 1, characterized in that: The amount of the small material taken out in step (3) is 10%-20% of the amount of the mixture prepared in step (2).

7. The method for preparing granite with granular through-texture according to claim 1, characterized in that: In the color paste described in step (4), the ratio of unsaturated polyester resin to iron-based pigment is 2:3-1:

1.

8. The method for preparing granite with granular through-texture according to claim 1, characterized in that: The amount of the curing agent added in step (5) is 1.0%-1.3% of the amount of the unsaturated polyester resin added in step (4), and the amount of the accelerator is 0.2%-0.5% of the amount of the resin. The viscosity of the prepared color paste is 900-1800mPa.S.

9. The method for preparing granite with granular through-texture according to claim 1, characterized in that: The vacuum degree during the vacuuming in step (7) is 0.093-0.097 Mpa, and the pressing time after shaking is 25-35 seconds.

10. A granite with granular through-texture prepared according to the method according to any one of claims 1 to 9.